EDUCAÇÃO FISICA ESCOLAR NO IMAGINÁRIO DA GESTÃO ESCOLAR DA CIDADE DE BURITI DOS LOPES-PI - Vieira de Carvalho de Souza, Sabina; Luiz Duarte Val, George; Cesar da Silva Oliveira, Edvaldo (Revista Form@re - Parfor/UFPI, 2026)
.